2015
DOI: 10.1186/s13044-015-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Rare thyroid non-neoplastic diseases

Abstract: Rare diseases are usually defined as entities affecting less than 1 person per 2,000. About 7,000 different rare entities are distinguished and, among them, rare diseases of the thyroid gland. Although not frequent, they can be found in the everyday practice of endocrinologists and should be considered in differential diagnosis. Rare non-neoplastic thyroid diseases will be discussed. Congenital hypothyroidism’s frequency is relatively high and its early treatment is of vital importance for neonatal psychomotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Fetal dyshormonogenetic goiter is a rare disease characterized by increased fetal thyroid gland size due to inherited defects in genes that control thyroid hormone synthesis and transportation. The incidence varies between 1:30,000 and 1:50,000 live births in the European and North American regions, and it accounts for up to 15% of congenital hypothyroidism cases (1,2). It affects predominantly female fetuses (male:female ratio, 1:2) and has no racial or ethnic predilection, but it is encountered more often in consanguineous couples (3).…”
Section: Introductionmentioning
confidence: 99%
“…Fetal dyshormonogenetic goiter is a rare disease characterized by increased fetal thyroid gland size due to inherited defects in genes that control thyroid hormone synthesis and transportation. The incidence varies between 1:30,000 and 1:50,000 live births in the European and North American regions, and it accounts for up to 15% of congenital hypothyroidism cases (1,2). It affects predominantly female fetuses (male:female ratio, 1:2) and has no racial or ethnic predilection, but it is encountered more often in consanguineous couples (3).…”
Section: Introductionmentioning
confidence: 99%
“…With fewer than 70 cases reported in the medical literature, thyroid sarcoidosis is most commonly identified during postmortem, with a prevalence of only 1%–4% of those with systemic disease 14 15. Thyroid sarcoidosis has been associated with solitary hypoechoic nodules, Hashimoto’s, Graves’ disease with resistance to radioiodine, hypothalamic–pituitary involvement with secondary hypothyroidism or diffuse infiltration, with or without deranged hormonal status, as in this case 16–20…”
Section: Discussionmentioning
confidence: 91%
“…Hypothyroidism is associated with disturbed cytokine concentrations, an abundance of reactive oxygen species (ROS), and altered signal transduction in most parts of the brain (53). In addition, chronic inflammation plays an important role in the pathogenesis of many diseases, including hypothyroidism (54). A recent experimental study in female rats found that PM 2.5 exposure reduces circulating thyroid hormone levels by interrupting thyroid hormone biosynthesis, biotransformation, and transport; by inducing oxidative stress and inflammatory responses; and ultimately by activating the hypothalamicpituitary-thyroid axis and inducing the production of hepatic transthyretin (55).…”
Section: Discussionmentioning
confidence: 99%